Tribal labour in India - Tripathy, S. N. (ed.) (New Delhi, 1997)
This work, Tribal Labour in India, contains seven contributions of eminent writers including one writeup of the editor. This volume examines the socio-economic and dimensional problems of trival emerging out of industriali sation and urbanisation. Issues like consumption pattern, government policy and rehabilitation strategy have also been dealt with. Undoubtedly, the book will be immensely beneficial to the administrators, demographers, policy makers, planners and researchers.
Keywords: Labour and labouring class India